Pemberdayaan Keluarga Dalam Proses Perawatan Klien Skizofrenia Melalui Pendidikan Kesehatan Di Rumah Sakit Jiwa - Makassar Muhammad Nur, Muhana Sofiati Utami dan Supriyati (Berita Kedokteran Masyarakat (BKM), 2004)
Background: At Makassar Mental Hospital, there are 72,84% clients hospitalized were schizophrenia. Family and social support is an important factor that influences the schizophrenia therapy. However, family and social support for the client is poor. It s because knowledge, attitude, and client s family practice toward schizoprenia is poor. Objective: This research was aimed to find out the influence of the family empowerment by group health education and individual health education using folder toward family knowledge, attitude, and practice in schizophrenia client treatment. Methods: This research was a quasi experimental study by nonequivalent control group with pretest and post test design. The subjects were 60 people of schizophrenia client s families treated in intensive service Unit Makassar Mental Hospital. 30 people of them were empowered by group health education using folder, and the other one were empowered by individual health education using folder. Results: Analysis of paired t-test from pre test to post test 1 and post test 2 showed that the both method increased knowledge, attitude, and behavior of schizophrenia client family effectively in treatment. Yet, on analysis of independent t-test, method of group espionage used folder was more effective than individual espionage method used folder for increasing knowledge. Conclusion: Family empowerment by group and individual health education using folder were effective to increase schizophrenia client s family knowledge, attitude, and practice in schizophrenia client treatment. Keywords: health education, schizophrenia treatment, client s family, family empowerment